Local Order and Conflict in Colombian Northwest. Nariño (Antioquia), Riosucio (Chocó) and San Pedro de Urabá, 1991-2010 - García, Clara Inés; Aramburo, Clara Inés; Domínguez, Juan Camilo (Sociedad y Economía, 2016)
This paper investigates how local orders were re configured in territories with highestlevel of armed confrontation in Colombia between 1991 and 2010, what factors determinethose reconfigurations, and what specific type of local orders have resulted. Based on theconcept of social order, one typology created from the crossing of categories of coercionand agency, and a comparative approach inspired by complex configuration of explanatoryfactors of Charles Ragin, the article states the results shown by the study of thethree cases discussed in terms of the reconfiguration of these three local orders, and theoutstanding differences that show these localities in its ability to meet the conditions ofarmed confrontation.